The multiple-theories problem: The case of spatial industrial clustering - Marchionni Caterina; Oinas Päivi (SAGE PUBLICATIONS INC, 2025)
Multiple theories of the same phenomenon abound in many interdisciplinary research areas, but it
is often unclear how the theories relate, and there are no clear guidelines for dealing with this
plurality. The history of research on spatial industrial clustering is a case in point. We identify a
number of solutions to the problem of multiple theoretical accounts proposed in this literature.
We label them definitional, taxonomic, integrative, and multi-perspectival. We then offer the
erotetic solution as an indispensable complement to any attempt at resolving the multiple-theories
problem. It accounts for theoretical plurality in terms of different explanation-seeking questions
different theories aim to address. We analyse three prominent explanations in the recent history
of research on spatial industrial clustering and show how the erotetic approach can contribute to
foster interdisciplinary dialogue.